10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Blastocystis sp. is a predominant anaerobic eukaryote of the human gastrointestinal tract, with carriage rates exceeding 50% in some populations, particularly in low- and middle-income countries, using molecular methods. Despite its widespread occurrence, its clinical importance continues to be a matter of debate because of its genetic diversity [having 44 subtypes (STs)] and its varied associations with host pathology. SCOPE: This review summarizes recent findings (2021-2026) on the epidemiology, transmission, pathogenicity, host-microbiome interactions, and subtype-specific characteristics of Blastocystis, with emphasis on its dual role in human health. KEY FINDINGS: Current evidence indicates that Blastocystis may be either pathogenic or completely commensal, depending on diverse factors. It may be a reflection of a particular gut ecosystem, including higher bacterial diversity and ecological stability. Certain virulence mechanisms of the parasite can disrupt immune responses and epithelial integrity. Virulence related to STs and other factors may be responsible for the shift from asymptomatic colonization to disease, along with the immune status of the host and microbial environment. Blastocystis may be beneficial in healthy conditions, but may cause increased complications in dysbiosis states. Transmission of the infection may be from contaminated water, edible plants, and animal products. CONCLUSION: Understanding the dual roles of Blastocystis requires comprehensive studies that address subtype-specific behavior and context-dependent host interactions. The present review presents a broad overview of the parasite and further directions for research.